Enhancement of Precise Gene Editing by the Association of Cas9 With Homologous Recombination Factors - Tran, Ngoc-Tung; Bashir, Sanum; Li, Xun; Rossius, Jana; Chu, Van Trung; Rajewsky, Klaus; Kühn, Ralf (Frontiers in Genetics, 2019)
The CRISPR-Cas9 system is used for genome editing in mammalian cells by introducing double-strand breaks (DSBs) which are predominantly repaired via non-homologous end joining (NHEJ) or to lesser extent by homology-directed repair (HDR). To enhance HDR for improving the introduction of precise genetic modifications, we tested fusion proteins of Cas9 nuclease with HDR effectors to enforce their localization at DSBs. Using a traffic-light DSB repair reporter (TLR) system for the quantitative detection of HDR and NHEJ events in human HEK cells we found that Cas9 fusions with CtIP, Rad52 and Mre11, but not Rad51C promote HDR up to two-fold in human cells and significantly reduce NHEJ events. We further compared, as an alternative to the direct fusion with Cas9, two components configurations that associate CtIP fusion proteins with a Cas9-SunTag fusion or with guide RNA that includes MS2 binding loops. We found that the Cas9-CtIP fusion and the MS2-CtIP system, but not the SunTag approach increase the ratio of HDR/NHEJ 4.5 - 6-fold. Optimal results are obtained by the combined use of Cas9-CtIP and MS2-CtIP, shifting the HDR/NHEJ ratio by a factor of 14.9. Thus, our findings provide a simple and effective tool to promote precise gene modifications in mammalian cells.